2016
DOI: 10.1177/2278533716644873
|View full text |Cite
|
Sign up to set email alerts
|

Employment Opportunities and Barriers on the Russian and German Labor Market for International Graduates with Domestic Degrees

Abstract: Assuming that employment prospects in the country of education represent a pull factor for international students to enroll in higher education programs abroad and a selling proposition for higher education institutions campaigning for international students, this study aims at investigating the validity of these prospects. Using a qualitative research approach, in-depth interviews were conducted with recruiters of 12 companies in Germany and Russia. A content analysis was applied to identify and compare emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Almeida et al, 2015;Carlsson and Rooth, 2007;Fernando et al, 2016), or the international orientation of the organization (e.g. Makkonen, 2017;Shchegolev et al, 2016). In these studies, similar to our case, local organizations associate migrants with factors such as a lower local human capital (Crowley-Henry and Al Ariss, 2018), thereby allowing migrants' perceived lack of knowledge about local practices and language to be linked to inefficient work habits (Makkonen, 2017).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Almeida et al, 2015;Carlsson and Rooth, 2007;Fernando et al, 2016), or the international orientation of the organization (e.g. Makkonen, 2017;Shchegolev et al, 2016). In these studies, similar to our case, local organizations associate migrants with factors such as a lower local human capital (Crowley-Henry and Al Ariss, 2018), thereby allowing migrants' perceived lack of knowledge about local practices and language to be linked to inefficient work habits (Makkonen, 2017).…”
Section: Discussionsupporting
confidence: 78%
“…Large organizations have more resources for screening candidates (see Almeida et al, 2015;Lundborg and Skedinger, 2016) and seem to be less concerned about migrants fitting the existing pool of employees or whether they will meet clients' expectations (Fernando et al, 2016;Lundborg and Skedinger, 2016). The international orientation of organizations also appears to matter in recognizing the benefits of hiring skilled migrants (Makkonen, 2017;Shchegolev et al, 2016).…”
Section: Organizational Factors Influencing the Perceived Employabili...mentioning
confidence: 99%
“…Li (2020), and Shumilova and Cai (2016) argued that Finnish employers must adapt to the needs of workers, such as operating in English, to remain competitive in the global market for highly skilled workers, as workers may leave the country if opportunities are not available. Shchegolev et al (2016) found that German companies have implemented mentoring and international trainee programmes to support international graduates and strategically recruit them. Coffey et al (2018) report that Japanese investors have recognised the necessity of providing employment visas to Chinese students studying in Japan to facilitate their work with Chinese businesses.…”
Section: Role Of Institutionsmentioning
confidence: 99%